Effect of Phosphorus and Sulphur on Growth and Yield of Soybean (Glycine max L.) - Akter, Fahmina; Islam, Md. Nurul; Shamsuddoha, A. T. M.; Bhuiyan, M. S. I.; Shilpi, Sonia (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted at Sher-e-Bangla Agricultural University Farm, Dhaka, Bangladesh from December 2008 to April 2009 to evaluate the effect of P (viz. 0, 15, 30, 50 kg P2O5 ha-1) and S (viz. 0, 10, 20, 40 kg S ha-1) and their interaction on the growth and yield of soybean (Glycine max L.). Individual application of different levels of phosphorus and sulphur showed significant effect on yield and yield attributes studied. Among them, plant height, number of primary branch plant-1, number of leaves plant-1, stover yield increased significantly up to 50 kg P ha-1. On the other hand, numbers of pods plant-1, number of seeds plant-1, thousand seed weight, grain yield, biological yield increased significantly up to 30 kg P ha-1. However, in case of S, the positve response was observed only upto 20 kg S ha-1. The combined application of phosphorus @ 30 kg P ha-1 and sulphur @ 20 kg S ha-1 gave rise to the highest number of pods plant-1 (30.07), number of seeds plant-1 (84.94), thousand seed weight ( 94.61 g), and in turn produced highest grain yield (2.29 t ha-1). Thus, the combined application of 30 kg Phosphorus ha-1 and 20 kg Sulphur ha-1 may be considered to be optimum for getting higher yield of soybean.